Social and Physical Context Moderates Older Adults' Affective Responses to Sedentary Behavior: An Ecological Momentary Assessment Study. (28th February 2021) - Hevel, Derek J; Drollette, Eric S; Dunton, Genevieve F; Maher, Jaclyn P
Abstract: Objectives: Older adults engage in excessive sedentary behaviors which hold significant health implications. Examining affect responses during sedentary behavior is not well understood despite the wealth of evidence linking affect and motivation. Contextual influences (i.e., social and physical) likely influence affective responses during sedentary behavior and therefore warrant further investigation. Method: Older adults ( n = 103, M age = 72, range: 60–98) participated in a 10-day study where they received 6 randomly timed, smartphone-based Ecological Momentary Assessment (EMA) prompts/day. Participants reported their affect, current behavior, and context at each EMA prompt. Participants also wore an activ PAL accelerometer to measure their sedentary behavior duration. Separate multilevel models examined the extent to which the context influences affective responses during self-report sedentary (vs nonsedentary) behaviors. Results: The social context moderated the association between sedentary behavior and negative affect. The physical context moderated the association between sedentary behavior and positive affect. Discussion: Interventions should consider the context of behaviors when designing interventions to reduce sedentary behavior as some contextual factors may attenuate, while other contexts may exacerbate, associations between activity-related behaviors and indicators of well-being.